Passivation of native defects of ZnO by doping Mg detected through various spectroscopic techniques - Singh V.P.; Rath C. (My University, 2025)
Native defects, responsible for the n-type behavior of ZnO are found to be reduced by Mg doping. Zn1-xMgxO nanoparticles synthesized by the conventional coprecipitation route are characterized by XRD, TEM and various spectroscopic techniques like FTIR, XPS, UV-visible, PL, Raman and PAS. Unintentional hydrogen and complex defects in addition to cationic and anionic vacancies (VZn and VO) in ZnO nanoparticles are observed from FTIR. After incorporating Mg, an additional IR mode at 856 cm-1 is observed and attributed to Mg-H. The additional mode contributing excess hydrogen in Mg doped ZnO is further confirmed from XPS. PL and PAS measurements indicate less native defects in Mg doped ZnO because of passivation of defects by excess hydrogen. We conclude that Mg doping not only diminishes the native defects in ZnO, but also could be used as a suitable material for hydrogen storage. © The Royal Society of Chemistry 2015.